The Invocations - Sutherland, Krystal (New York : Nancy Paulsen Books, 2024)
"To get what they want most, Zara and Jude search for Emer, an orphaned witch with dark and deadly powers, but when a serial killer targets Emer's clients, the three girls form an uneasy alliance to hunt the killer before they meet the same fate"
Keywords: Witches -- Juvenile fiction; Magic -- Juvenile fiction; Orphans -- Juvenile fiction; Serial murderers -- Juvenile fiction; Friendship -- Juvenile fiction